Sex differences in management and outcomes of patients with type 2 diabetes and cardiovascular disease: A report from TECOS. Issue 10 (19th June 2018) - Alfredsson, Joakim; Green, Jennifer B.; Stevens, Susanna R.; Reed, Shelby D.; Armstrong, Paul W.; Angelyn Bethel, M.; Engel, Samuel S.; McGuire, Darren K.; Van de Werf, Frans; Hramiak, Irene; White, Harvey D.; Peterson, Eric D.; et al.
Abstract : Aim: To examine sex differences in baseline characteristics and outcomes in patients with type 2 diabetes and atherosclerotic vascular disease. Materials and methods: Cox models were used to analyse the association between sex and outcomes in the Trial Evaluating Cardiovascular Outcomes with Sitagliptin (TECOS), a randomized, placebo‐controlled trial assessing the impact of sitagliptin on cardiovascular (CV) outcomes in patients with type 2 diabetes and atherosclerotic vascular disease. Results: A total of 4297 women and 10 374 men were followed for a median of 3.0 years. Women were slightly older and more often had cerebrovascular disease and peripheral arterial disease but less often coronary heart disease than men. At baseline, women were less likely to use aspirin or statins. The primary composite outcome of CV death, myocardial infarction, stroke, or hospitalization for unstable angina occurred in 418 women (9.7%) and 1272 men (12.3%; 3.48 vs 4.38 events/100 participant‐years, crude hazard ratio [HR] 0.79, 95% confidence interval [CI] 0.71‐0.89, adjusted HR 0.64, 95% CI 0.55‐0.74; P < .0001). Women also had a significantly lower risk of secondary CV outcomes and all‐cause death. Conclusions: In this large prospective study of people with type 2 diabetes and CV disease, women had different CV disease burden, worse CV risk factor profiles, and less use of indicated medications than men. Despite this, women had significantly lower risk of CV events, suggesting that the cardioprotective effects of female sex extend to populations with type 2 diabetes.